The rise of independence feelings in Catalonia and Scotland. A longitudinal study on the profile of independence in the beginning of the 21st century - Merino, Javier Antón (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The following article aims to make headway on the knowledge related to the elements that explain the steep increase of secessionist nationalism during the 21st century in the peripheral territories of plurinational Western long-established democracies, such as the ones existing in the United Kingdom and Spain. In order to do so, we will be focusing on the quick change observed in the preferences as to the state territorial organization in Catalonia and Scotland. Through the usage of the logistic regression technique, a longitudinal analysis will be carried out to analyze the principal characteristics of the Catalonian and Scottish independence profile throughout the period comprehended between 1999 and 2016.
Keywords: Catalonia; Scotland; secessionism; logistic regression